Strategic use of available capacity in the electricity spot market - Chloé LeCoq (Stockholm School of Economics, The Economic Research Institute (EFI), 2002)
The literature on deregulated electricity markets generally assumes available capacities to be given. In contrast, this paper studies a model where firms precommit to capacity levels before competing in a uniform price auction. The analysis sheds light on recent empirical findings that firms use their available capacity to obtain high market prices. There exist two equilibria where at least one firm withholds its available capacity to induce the maximum price. Moreover, in one equilibrium, the inefficient firm obtains a relatively large market share.
Keywords: C72; D43; D44; L13; L94; 330; spot market; capacity game; auction mechanism; electricity; Elektrizitätswirtschaft; Deregulierung; Kapazitätsplanung; Auktion; Spieltheorie